Ectonucleoside Triphosphate Diphosphohydrolase-1/CD39 Affects the Response to ADP of Female Rat Platelets - Caiazzo, Elisabetta; Bilancia, Rossella; Rossi, Antonietta; Ialenti, Armando; Cicala, Carla (Frontiers in Pharmacology, 2020)
There is evidence that an imbalance of extracellular purine levels may be associated with increased cardiovascular risk. Platelets play a pivotal role in vascular homeostasis and thrombosis and are important source of purine nucleotides and nucleosides. Hydrolysis of nucleotides ATP and ADP is regulated by two ectonucleotidase, triphosphate diphosphohydrolase-1 (NTPDase-1/CD39) and ecto-5’-nucleotidase, (ecto-5’-NT/CD73). CD39 enzyme is expressed on the endothelium, circulating blood cells and smooth muscle cells; there is evidence that changes in CD39 expression and activity affects the potential thrombogenic of a tissue. Gender difference in the cardiovascular risk has been extensively observed; however, while the age–dependent difference in the prevalence of cardiovascular events between man and women has been attributed to the loss of the protective effect of estrogens in the postmenopausal period, the physiological mechanism behind gender disparity is still unclear. Here, we evaluated comparatively male and female rat platelet reactivity and considered the possible role of CD39 at the basis of difference observed. We found a reduced in vitro response to ADP (1 – 30 µM) of female compared to male platelets, associated to increased platelet CD39 expression and activity. Platelets response to ADP was strongly increased by incubation (10 min) with the CD39 inhibitor, ARL67156 (100 µM), while male platelets response was unaffected. Rat treatment with clopidogrel (30 mg/kg, per os) inhibited ex vivo platelet aggregation. Bleeding time was prolonged in female compared to male. Taken together our results suggest that platelet ATPase and ADPase activity might be a reliable predictor of platelet reactivity.